Pedagogia na colina : A faculdade Adventista de educação da universidade Adventista de São Paulo de 1971 a 1999 - Klein, Débora (2008)
This research studies the process of the constitution of the Adventist Education University of the nowadays known as São Paulo Adventist University Center, presenting its particularities in the institutional structure and teaching formation. Special attention is given to the Pedagogy class of the FAED 1994. This work is inserted in the research line about the history of Scholar Instituitions. For the fulfillment of this investigation the following methodological procedures were used: the analyses of documents of the Institution, participative observation, independent observation, interviews with teachers, directors, specialist and ex-students of three different classes of the FAED.